Analysis of GATA1 mutations in Down syndrome transient myeloproliferative disorder and myeloid leukemia. - Alford, K; Reinhardt, K; Garnett, C; Norton, A; Böhmer, K; von Neuhoff, C; Kolenova, A; Marchi, E; Klusmann, J; Roberts, I; Hasle, H; Reinhardt, D; et al. (2011)
Children with Down syndrome (DS) up to the age of 4 years are at a 150-fold excess risk of developing myeloid leukemia (ML-DS). Approximately 4%-5% of newborns with DS develop transient myeloproliferative disorder (TMD). Blast cell structure and immunophenotype are similar in TMD and ML-DS. A mutation in the hematopoietic transcription factor GATA1 is present in almost all cases. Here, we show that simple techniques detect GATA1 mutations in the largest series of TMD (n = 134; 88%) and ML-DS (n = 103; 85%) cases tested. Furthermore, no significant difference in the mutational spectrum between the 2 disorders was seen. Thus, the type of GATA1 sequence mutation is not a reliable tool and is not prognostic of which patients with TMD are probable to develop ML-DS.